Let X = {2, 4, 5, 6} Y = {3, 4, 7, 8} Z = {5, 6, 7, 8}, find
(a) (X - Y) ∪ (Y – X) (b) (X - Y) ∩ (Y - X)
(c) (Y - Z) ∪ (Z – Y) (d) (Y - Z) ∩ (Z – Y)
Answers
ANSWER
(2,3,5,6,7,8)
Step-by-step explanation:
- first we have to cancel the same element in the both side.
- And then write the first one
- (2,5,6)U(3,7,8)
- JOIN the elements together
- the answer will get
Therefore the answers are
(a) {,2,5,6,3,7,8} (b) {}
(c) {3,4,5,6} (d) {}
Given:
X = {2, 4, 5, 6}, Y = {3, 4, 7, 8}, Z = {5, 6, 7, 8}
To find:
(a) (X - Y) ∪ (Y – X) (b) (X - Y) ∩ (Y - X)
(c) (Y - Z) ∪ (Z – Y) (d) (Y - Z) ∩ (Z – Y)
Solution:
Given X = {2, 4, 5, 6}, Y = {3, 4, 7, 8}, Z = {5, 6, 7, 8}
(a) (X - Y) ∪ (Y – X)
⇒ (X - Y) = {2, 4, 5, 6} - {3, 4, 7, 8} = { 2, 5, 6}
⇒ (Y – X) = {3, 4, 7, 8} - {2, 4, 5, 6} = {3, 7, 8}
⇒ (X - Y) ∪ (Y – X) = {2,5,6,3,7,8}
(b) (X - Y) ∩ (Y - X) = { 2, 5, 6} ∩ {3,7,8} = {2,5,6,3,7,8}
⇒ (X - Y) ∩ (Y - X) = {}
(c) (Y - Z) ∪ (Z – Y)
(Y – Z) = {3, 4, 7, 8} – {5, 6, 7, 8} = {3,4}
(Z – Y) = {5, 6, 7, 8} – {3, 4, 7, 8} = {5,6}
⇒ (Y - Z) ∪ (Z – Y) = {3,4,5,6}
(d) (Y - Z) ∩ (Z – Y) = {3,4} ∩ {5,6} = {}
⇒ (Y - Z) ∩ (Z – Y) = {}
Therefore the answers are
(a) (X - Y) ∩ (Y - X) = {,2,5,6,3,7,8}
(b) (X - Y) ∩ (Y - X) = {}
(c) (Y - Z) ∪ (Z – Y) = {3,4,5,6}
(d) (Y - Z) ∩ (Z – Y) = {}
#SPJ2